2019
DOI: 10.1111/neup.12560
|View full text |Cite
|
Sign up to set email alerts
|

Microglia: Lifelong modulator of neural circuits

Abstract: Microglia, the sole immune cells in the brain, are the key player for synaptic regulation required for our brain function in both developing and adult brain. They have highly motile processes to detect synaptic functions. Recent accumulated studies have unveiled the mechanism underlying synapse detection and pruning / formation by microglia. In this review, we summarize the current knowledge of various microglial machinery recruited in synaptic modulation in the different life stages and contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…Microglial cells play a key role in the maintenance of brain homeostasis from early development to adulthood, including neurodevelopment, synaptic pruning, neuronal circuit maturation [ 20 , 21 ], and the impairment of microglial functions which can lead to severe pathological outcomes.…”
Section: Microglia Function In Health and Prion Diseasesmentioning
confidence: 99%
“…Microglial cells play a key role in the maintenance of brain homeostasis from early development to adulthood, including neurodevelopment, synaptic pruning, neuronal circuit maturation [ 20 , 21 ], and the impairment of microglial functions which can lead to severe pathological outcomes.…”
Section: Microglia Function In Health and Prion Diseasesmentioning
confidence: 99%
“…As the sole immune cells in the brain, microglia play essential roles in maintaining brain functions by plays sentinel, housekeeping function and defense roles (Wolf et al, 2017;Hickman et al, 2018). Microglia strongly influence the pathologic outcomes in non-infectious pathological states (Ramirez et al, 2017;Ikegami et al, 2019) and acts as pivotal mediators of neuroinflammation via the release of cytokines, chemokines, and growth factors in various infectious diseases to regulate innate immunity and participate in adaptive immune responses in CNS tissue (Colonna and Butovsky, 2017). Our previous work indicated that microglial activation, which is considered a main target for therapeutic interventions for a variety of CNS diseases (Heppner et al, 2005;Garden and Möller, 2006), appears to be one of the checkpoints in CNS inflammation caused by A. cantonensis infection (Zhao et al, 2013;Wei et al, 2015), and the administration of minocycline, an inhibitor of microglial activation, is effective in treating mice infected with A. cantonensis (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…However, synaptic plasticity does not only involve only neurons but also interactions with glial cells such as astrocytes and microglia [162]. Microglia are key regulator of neurodevelopment, neuroinflammation, and BBB integrity [167]. An important mechanism involved in cognition is microglia-dependent synaptic removal, which allows synapse remodeling called synapse pruning [167].…”
Section: Arbovirus and Modulation Of Synaptic Functionmentioning
confidence: 99%
“…Microglia are key regulator of neurodevelopment, neuroinflammation, and BBB integrity [167]. An important mechanism involved in cognition is microglia-dependent synaptic removal, which allows synapse remodeling called synapse pruning [167]. This mechanism, when exacerbated, can cause cognitive dysfunction [168,169].…”
Section: Arbovirus and Modulation Of Synaptic Functionmentioning
confidence: 99%